Non-Discrimination of Children - Kornel, Martin (Children’s Rights in Regional Human Rights Systems, 2024)
This chapter discusses the historical roots of discrimination against children, including explorations about factors such as origin, gender, race, and birth status, and highlights the persistent forms of discrimination in areas such as education, gender-based practices, and social and economic rights. It provides a general outline of the evolution of the principle of the non-discrimination of children in international and regional instruments. The text outlines key discrimination concepts such as the distinction between accessory and autonomous rights, the state’s negative and positive obligations to combat discrimination, formal versus substantive equality, prohibited grounds for discrimination, and various forms of discrimination, including direct, indirect, and discrimination by association. The application of the discrimination test according to Art. 14 of the ECHR in cases involving minors is explained in detail. First, the method used to assess the differences in treatment is clarified, and then it is explored how the European Court of Human Rights examines whether such differences are objectively justified (based on the legitimate aim and proportionality criteria).Keywords:  Non-Discrimination of Children; Discrimination Test; Prohibited Grounds; Difference in Treatment; Legitimate Aim; Proportionality